Two Records of Relative Paleointensity for the Past 4 Myr - Valet, Jean-Pierre; Thevarasan, Anojh; Bassinot, Franck; Savranskaia, Tatiana; Haddam, Naoufel (Frontiers in Earth Science, 2020)
We performed new high-resolution magnetic measurements of sedimentary cores from the east northern Pacific ODP site 1021 and the East equatorial Pacific ODP site 851. ODP site 1021 is characterized by a high clay content with less than 10% carbonates in contrast to site 851 which is highly carbonated (% CaCO3 of at least 70%). The time scale of both records was obtained by orbital tuning of sediment density and/or susceptibility variations and whenever possible tested against the reversal positions. Previous magnetic studies at both sites have been concentrated on the past 1.2 Ma using U-channels. We extended this period and performed high resolution and detailed studies of 4210 sediment levels that cover the past 4.4Ma. Natural Remanent Magnetization (NRM) and Anhysteretic Remanent Magnetization (ARM) were both stepwise demagnetized by alternating fields. The new results confirm the magnetostratigraphy derived from the shipboard measurements but improve the definition of the polarity intervals and identify zones or events that were either unclear or hidden by unremoved secondary components. Studies of relative paleointensity were conducted following the standard rules and yielded determinations with the exception of intervals that were either too weakly magnetized or disturbed. The evolution of relative paleointensity displays similar behavior during the reversal periods at both sites, but the two curves show strikingly different patterns outside the transitional intervals that are characterized by the largest intensity changes. Spectral analyses revealed that magnetic concentration was strongly dependent on paleoenvironmental components at ODP site 1021 which likely affected the results of relative paleointensity. It is assumed that the absence of any long-term geomagnetic trend during the stable polarity intervals at this site results from the interplay between climatic and geomagnetic factors. The large amplitude of field intensity decrease during the reversal periods dominates all other factors and is thus visible over the entire record.